LEADER AGGRESSIVE HUMOR AND EMPLOYEE OUTCOMES: THE MODERATING ROLE OF LMX - Ya-Ci Wang, (PEOPLE: International Journal of Social Sciences, 2026)
Based on the approach-avoidance framework, this study examines the effect of leaders’ aggressive humor on employees’ avoidance tendencies and further investigates how these avoidance tendencies influence employees’ work engagement. Additionally, leader-member exchange (LMX) is incorporated as a moderator in the relationship between avoidance tendencies and work engagement. We collect data through a questionnaire survey administered to full-time employees across various industries and job roles to enhance the generalizability of the findings. This study hypothesizes that aggressive humor increases employees’ avoidance tendencies (H1), avoidance tendencies reduce work engagement (H2), and LMX moderates the relationship between avoidance tendencies and work engagement (H3). The findings are expected to clarify the mechanism through which aggressive humor affects employees and offer practical implications for leader selection, leadership training, and strategies for enhancing work engagement.